EFEK MODERASI KOMPENSASI PADA PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN BPR DI WILAYAH KABUPATEN KARANGANYAR - Praptiestrini . (Universitas Sahid Surakarta, 2019)
This study aims to (1) analyze significantly effect of the motivation, job satisfaction and compensation on employee performance; (2) analyze the role of compensation as a moderator of the effect motivation on employee performance; (3) analyze the role of compensation as a moderator of the effect job satisfaction on employee performance. This research using sample 65 marketing department employees at BPR in Karanganyar District. Data collecting with questionaire technique through validity and reliability test. The data analyse use the multiple regression analysis and moderated regression analysis through standardized residual method, and previously the researcher using classical assumption test. Results of this research showed that (1) motivation, job satisfaction and compensation have a significantly effect on employee performance. (2) compensation has moderate the effect of motivation to employee performance. (3) job satisfaction has not moderate the effect of job satisfaction on employee performance.